Pengembangan Video Motivasi Untuk Meningkatkan Literasi Peserta Didik Pada Pembelajaran PAI di SMK Nurul Qur’an Pati - Partono Partono (Tarbawiyah Jurnal Ilmiah Pendidikan, 2020)
Writing this paper entitled "Development of Video Motivation to Increase Student Literacy in Islamic Learning in Madrasah Aliyah". This writing aims to produce innovative and contextual learning media for the material presented and so that students are also able to literate in understanding the purpose of the video content independently. Islamic Learning is successful in supporting students to be able to answer the purpose of the lesson, the ability of individuals to process information, and knowledge for life skills called literacy. In developing the evaluation of this paper, the writer uses the literature study method. Based on the data from the study results, it can be seen that the learning media based on audiovisual or video that does not motivate students can improve the ability of students to titrate. Can the objectives of learning Islam can be achieved.